Geopolitical view of Ukraine: History of development and specifics of its current transformation - Kopachinska, Galina (Quaestiones Geographicae, 2021)
The main task of the research was to investigate and differentiate the historical stages of the formation of Ukraine’s geopolitical view, based on the Ukrainian statehood history and works of key researches, which had been directly influenced by the evolution of its geopolitical consciousness and thinking. In the article, three main historical stages of Ukraine’s geopolitical view formation were differentiated and the reason why the state’s geopolitical view gradually transformed into the state’s geopolitical interest after Ukraine attained independence was substantiated. The article includes a SWOT analysis of Ukraine’s geopolitical location, based on which the state’s geopolitical interests of local, regional and global levels were represented. As Ukraine is in the field of geopolitical orientation of many countries not only in Europe but also around the world, the study of the state’s geopolitical view formation and current transformation is topical and can be useful for foreign researchers.